6*(9^(1/x))-13*(6^(1/x))+6*(4^(1/x))=0

4 answers

You have powers of 2 and 3. Expand all the groups, collect the powers, and solve for x.

If you get stuck, show what you got done.
I understand how to do it but am having trouble with the mathematical aspect. I have redone the problem quite a few times but keep getting stuck. Could you help?
It's annoying how you don't want to show your work. Just let us take care of it all.

Just for readability, try letting u = 1/x. Then you have

6*(9^u)-13*(6^u)+6*(4^u))=0
6*3^(2u) - 13*3^u*2^u + 6*2^(2u)

Now if you let v=3^u and z=2^u you have

6v^2 - 13vz + 6z^2 = 0
(3v-2z)(2v-3z) = 0

3v = 2z
3^(u+1) = 2^(u+1)
true only if u+1=0, or u=-1 so, 1/x = -1, x = -1

2v = 3z
2*3^u = 3*2^u
3^(u-1) = 2^(u-1)
true only if u-1=0 or u=1, so x=1

So, the two solutions are x = -1, 1

Sometimes you just have to make things easier to read to wade through the noise.
let assume that 1/x ( it is easy for me to write it down)
6*(9^(1/x))-13*(6^(1/x))+6*(4^(1/x))=0
turn out : 6*9^a-13*6^a+6*4a^a=0
divide 9^a to the function
6-13*(2/3)^a +6*(4/9)^a=0 ([2/3]^2=4/9)
=> 6-13*(2/3)^a + 6(2/3)^2a=0
now you can see out function looks like : ax^2+bx+c=0 so just put it into the calculator and we ge two solotion
first :2/3^a = 2/3 <=>a=1 <=>1/x=1 => x=1
second: 2/3^a =3/2<=>a=-1 <=> x=-1

in this problem, you just need to divide for 9^(1/x) or 4^(1/x) and it turn out the function ax^2 +bx+c .